Reactive dyeing of polyamide 6.6 by plasmatic modification - Oliveira, F. R. (2008)
Polyamide 6.6 fabrics were treated with plasmatic discharge obtained at atmospheric conditions in a DBD semi-industrial machine. Modifications in polyamide were evaluated, namely wettability by contact angle measurement and detection of changes in second order transitions by differential scanning calorimetry. The structural changes are responsible for the positive results obtained for reactive dyeing of polyamide after plasmatic treatment, achieving strong covalent bonding with the fiber. Excellent results are obtained in yield, leveling and fastness of reactive dyeing, meaning less dye in effluents, less time for dyeing processes, more consumer’s satisfaction, and the possibility to extend reactive dyeing to more intense colors in polyamide.